(untitled) (Research, Society and Development, 2020)
Nursing professionals are exposed to occupational risks on a daily basis that can compromise physical and mental health, interfere with quality of life and patient care. This study aimed to carry out a bibliographic survey on the most frequent diseases that affect nurses in the exercise of their profession, as well as to point out the associated factors. It is an integrative literature review, in which the following guiding question was formulated: “What are the main occupational diseases related to nursing work?”. For this purpose, the VHL (Virtual Health Library), Pubmed and SciELO databases were consulted. The studies available in their entirety, published in the years 2014 to 2019, in Portuguese, Spanish and English were used. This study showed that the main diseases that affect nurses are overweight, fatigue, low back pain, Burnout syndrome, musculoskeletal disorders and transmissible infections. The conditions that lead to the emergence of these injuries are related to the position that the professional occupies, a work sector with a higher level of demand and extended daily and weekly working hours. Therefore, the ways of coping to avoid the occurrence of these problems are psychological monitoring, ergonomic interventions, more time for leisure and rest, in view of preventive measures such as organization of the service sectors, use of PPE’s, communication skills, management of self-esteem and healthy eating.